Sport Specialization and Lower Extremity Injury Incidence: A Retrospective Pilot Study among Female Collegiate Soccer Players - Janae Anderson; Breanna Lewenthal; Suk-Kyu Kim; Jupil Ko (Asian Society of Kinesiology, 2018)
OBJECTIVES To assess the relationship between single sport specialization and lower extremity injury incidence among female collegiate soccer players. METHODS Five participants (5 females; age 19.6 ± 0.9 years) were recruited from a Division I college soccer team. No other inclusion criteria were included. Injury incidence was recorded on a dichotomous scale. Presence of a lower extremity injury that resulted in greater than 2 days of missed practice indicated a 'yes' for injury incidence. Zero reported injuries and injuries resulting in less than 2 days of missed practice indicated a 'no' for injury incidence. Sport specialization level was categorized on self-report questionnaire results. Participants were categorized as highly, moderately, lowly, or non-sport specialized. RESULTS Each participant was highly sport specialized (100%) and age of specialization ranged from 3 to 16 years old. Of the group total, three participants sustained a previous LEI that resulted in time-loss. An average of four days were lost due to injury. CONCLUSIONS A sample of five, highly sport specialized, female soccer players lost an average of four days due to lower extremity injury.